FEATURES OF INTRAOPERATIVE ADMINISTRATION OF ANTIBACTERIAL DRUGS FOR HIP JOINT ARTHROPLASTY IN PATIENTS WITH TUBERCULOSIS COXITIS - Rustamov, F.Kh.; Nazirov, P.Kh. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
to improve the results of hip arthroplasty in patients with tuberculous coxitis by developing measures to prevent suppurative septic complications. Material and methods: in order to develop measures for the prevention of septic complications, treatment outcomes were studied in 60 patients with tuberculosis coxitis, who were performed hip joint arthroplasty operations in the clinic of Republican Scientific Research Center of Phthisiology and Pulmonology in 2014-2018. Results: in all patients who underwent antibacterial therapy according to the proposed method, primary healing of postoperative wound was noted, postoperative complications were not observed. It was also found that, despite the high doses of the antibiotic, its concentration after a threefold administration decreases, to maintain the required level, its additional administration is required up to 6 times.Conclusions: The six-time antibiotic administration scheme developed by the authors maintains the therapeutic concentration of the drug in the blood and, therefore, prevents the development of paraprosthetic complications.